High BODE Index Score and Low Albumin Serum Level Identify Patients with Chronic Obstructive Pulmonary Disease (COPD) at Higher Risk for Complications after Major Lung Cancer Resection: A Retrospective Study - M.D. Ph.D., Gianluca Guggino; M.D., Guglielmo Monaco (International Journal of Innovative Research in Medical Science, 2017)
Introduction - Lung cancer is significantly more common in patients with chronic obstructive pulmonary disease (COPD) than in those without obstruction. Of note, in COPD patients, who underwent major resection for lung cancer, postoperative pulmonary complications and mortality are considerably frequent. Thus, accurate preoperative identification of risk factors for lung resection postoperative complications is greatly needed to improve COPD patient care. Materials and Methods - The study included 104 consecutive COPD patients who underwent pulmonary lobectomy for non-small cell lung cancer (NSCLC). Several functional and metabolic preoperative parameters were retrospectively evaluated and correlated with postoperative, not cardiovascular, complications and mortality occurring within 30 days after surgery or later if the patient was still hospitalized. Results - Two independent factors were associated with the occurrence of postoperative complications in COPD patients resected for lung cancer: the BODE index ≥3 (odd ratio, OR, 2.01; 95% confidence interval, CI, 1.07-3.925; p<0.001) and the albumin serum level <2.9 g/dL (OR 0.084; 95% CI 0.019-0.364; p<0.001). Conclusions - High BODE index score and low albumin serum level identify, among COPD patients who underwent major pulmonary resection for NSCLC, those at higher risk for postoperative complications. As the nutritional status significantly affects morbidity in COPD patients undergoing major lung resection for cancer, its preoperative improvement may be justified to reduce complications. Moreover, it could be considered an appropriate recommendation the measurement of the BODE index, a simple and low cost procedure, for better identify, before lung cancer resection, COPD patients at higher risk for complications and, thus, candidates for postoperative intensive care.